STUDY OF CHANGES IN OCCLUSAL SCHEME RESULTING FROM CREATING ARTIFICIAL TEETH IN THE DENTURE PATIENT WITH COMPLETE TOOTH LOSS AND ADVERSE CONDITIONS BY PROSTHETIC BED ON THE LOWER JAW - V.P. Nespryadko; V.Y. Krasnov; V. K. Paul (Ukrainian Medical Stomatological Academy, 2015)
According to many authors lingualized occlusion improves the stabilization of complete dentures especially in patients with bad conditions for the prosthetic tretment on the lower jaw. But the top of the palatal cusps of the acrylic posterior artificial teeth in lingualized occlusion increased pressure. As a result we have the transformation lingvalized occlusion to bilateral balanced occlusion. Composite artificial teeth are more resistant to abrasion but their cusps quickly erasedin lingualized occlusion. Disadvantages of porcelain artificial teeth in removable dentures are: only a mechanical, not a chemical compound with the plastic base of the prosthesis, the complexity of the occlusal adjustment, it is difficult to choose the set of porcelain teeth to create lingvalized occlusion because these teeth are produced mainly with classical 30 degrees cusps. The purpose of research is to assess the effect of the transformation lingualized occlusion to classical bilateral balanced occlusion (due to erase acrylic artificial teeth), the function of chewing and chewing efficiency of complete dentures in edentulous patients with bad conditions for the prosthetic tretment on the lower jaw. For the study we were involved 54 patients who had type 2 edentulous maxilla with Schroeder and 2 type of edentulous mandible with Kohler (severe resorbtion of the alveolar crest on the lower jaw). We divided the patients into 2 groups - basic (31 patiens) and control (23 patiens). In the control group metal overlay on artificial posterior teeth in prosthesis is not used, setting the teeth was carried out in semiajustable articulator Model 5000 (f. Bio - Art, Brazil) in lingvalized occlusion and also we used volumetric modeling for basis of mandibular complete denture. Position of edentulouse upper jaw was carried out in articulator using Professional face bow ( Bio - Art, Brazil). For patients from the main group we manufacture of complete denture and coating chewing surfaces 16, 26, 36, 46 artificial teeth cast metal overlay to inhibit erasure artificial teeth in complete dentures. In examination of patients in the control group after 6 months we found that abrasion of artificial teeth transform lingvalized occlusion to the classic bilateral balanced occlusion. The study of changes in the chewing function of the patients in main and control groups was performed by a computerized kinesiography of the lower jaw after 6 months of using prostheses . The study chewing patterns in patients from both studied groups showed statistically significant differences in the parameters that were analyzed in patterns of chewing. We studied such parameters of chewing pattern: 1) the number of chewing cycles until swallowing; 2) the total time of averaged chewing cycle; 3) the duration of each phase averaged chewing cycle (phase opening, closing phase, occlusal phase); Kinesiografic study of chawing jaw movements after 6 months of using prostheses showed less number of chewing cycles until swallowing, and lower the total duration of the average masticatory cycle and each of its phases compared with patients in the control group that we believe reflects the positive impact of lingvalized occlusion in complete denture stabilization and chewing function. We researched chewing efficiency using the method of Manly. We performed the examination of the patients during 1, 2 and 3 years after the installation of dentures in the oral cavity. In the control group - 3 year usage of complete dentures - the average chewing efficiency decreased by 21% compared with the first year of use. In the study group during the same period, the average chewing efficiency decreased by 8%. In our opinion, these results occur because of slowing erase acrylic teeth in complete dentures with metal overlays. We think that decrease chewing efficiency in the main group of a patients take place because of atrophy of the mandibular alveolar crest during complete denture function. The results of our research indicate that using the metal overlays on posterior artificial teeth preserving the effectiveness of chewing and continued lingvalized occlusion.